Initiatives of City Government of Calamba and Awareness of City on Plastic Dependency Reduction: Basis for Action Plan - Reyes, Ronn Martin (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to determine and understand the implementation and level of awareness regarding plastic dependency reduction initiatives by the City Government of Calamba. These initiatives were developed to decrease plastic usage and manage its disposal through public awareness and behavioral changes toward plastic usage and disposal. The study sought to explore the significant difference between the assessments of Barangay Residents and Calamba City Local Government on these initiatives and to evaluate the significant relationship between the implementation and the level of awareness of plastic dependency reduction in Calamba City. A total of 242 surveys were collected through a random sampling method utilizing a researcher-made survey form. The data were interpreted using composite mean, a Four Point Likert Scale, and Pearson Product-Moment Correlation. The results revealed a difference between the assessments of Barangay Residents and Calamba City Local Government on the City Government initiatives. Furthermore, the findings showed a significant relationship between the assessments of Barangay Residents and Calamba City Local Government authorities on the implementation of these initiatives and the level of awareness of plastic dependency reduction. Based on these findings, the researcher proposed an action plan and activities to be initiated by the City Environment and Natural Resources Office. These activities focus on public involvement and environmental awareness to improve the ongoing initiatives on plastic dependency reduction in the City of Calamba.